Philosophy and “science of education” in Italy in the early of the 20th century - D”™ArcangeliMarco Antonio (Opción, 2015)
The Rivista Pedagogica (1908-1939), founded and directed byLuigi Credaro (1860-1939), was the most important early 20th century Italian pedagogy journal. The Rivista developed Herbart”™s model of pedagogy, based on the means and goals of education being joined together while remaining separate entities, in a critical and anti-dogmatic view, combining the positivist approach to empirical and experimental sciences and the Kantian idea of the transcendental foundations of experience. The Rivista gave birth to an interpretation of the educational facts focused on such concepts as relationality and antinomicity and of the educational aims being strongly bound to their historical and social context, without attempting to replicate what already exists.